Engendering informality statistics: Gaps and opportunities - Jessica Gardner; Kieran Walsh; Michael Frosch (International Labour Organization (ILO), 2022)
Informality is a dynamic and multidimensional concern that demands gender-sensitive data. In 2018, globally, more than 60% of employment was informal. However, global averages hide that in more countries the share of women in informal employment exceeds that of men. Also, women in the informal economy are often in the most unprotected situations - as domestic workers, home-based workers and contributing family workers - where a lack of visibility can increase their vulnerability. The ILO and its partners are working to engender informality statistics to improve gender data and support countries to respond to data needs on women's economic empowerment. This working paper was written to support the ILO Working Group for the Revision of the standards for statistics on informality. It explores the demand for gender data on informality and the measurement challenges faced. The paper highlights the opportunities emerging from the revision of statistical standards on informality that are set to be adopted in 2023.
Keywords: 330; informal employment; informal economy; gender; statistics; labour statistics